Hygroscopic properties of urban aerosols and their cloud condensation nuclei activities measured in Seoul during the MAPS-Seoul campaign. (March 2017) - Kim, Najin; Park, Minsu; Yum, Seong Soo; Park, Jong Sung; Song, In Ho; Shin, Hye Jung; Ahn, Joon Young; Kwak, Kyung-Hwan; Kim, Hwajin; Bae, Gwi-Nam; Lee, Gangwoong
Abstract: Aerosol physical properties, chemical compositions, hygroscopicity and cloud condensation nuclei (CCN) activities were measured in Seoul, the highly populated capital city of Korea, during the Megacity Air Pollution Studies (MAPS-Seoul) campaign, in May–June 2015. The average aerosol concentration for particle diameters >10 nm was 11787 ± 7421 cm −3 with dominant peaks at morning rush hours and in the afternoon due to frequent new particle formation (NPF) events. The average CCN concentration was 4075 ± 1812 cm −3  at 0.6% supersaturation, with little diurnal variation. The average hygroscopicity parameter ( κ ) value determined using a humidified tandem differential mobility analyzer (HTDMA) ranged 0.17–0.27 for a range of particle diameters (30–150 nm). The κ values derived using the aerosol mass spectrometer (AMS) data with three different methods were 0.32–0.34, significantly higher than those from HTDMA due to the uncertainties in the hygroscopicity values of different chemical compositions, especially organics and black carbon. Factors affecting the aerosol hygroscopicity seemed to be traffic and chemical processes during the NPF events. The CCN concentration predicted based on HTDMA κ data showed very good agreement with the measured one. Because of the overestimation of κ, CCN closure with the predicted CCN concentration based on AMS κ data over-predicted CCN concentration although the linear correlation between measured and predicted CCN concentration was still very good. Highlights: Comprehensive aerosol physical, chemical properties were measured in Seoul, Korea. Aerosol number concentrations showed a dominant peak in the afternoon. Hygroscopicity varied diurnally especially for small particles. Predicted CCN concentration using HTDMA data matched well with the measured one.